The mTOR signaling pathway in the prefrontal cortex is compromised in major depressive disorder - Jernigan, Courtney S.; Goswami, Dharmendra B.; Austin, Mark C.; Iyo, Abiye H.; Chandran, Agata; Stockmeier, Craig A.; Karolewicz, Beata (Progress in neuro-psychopharmacology & biological psychiatry, 2011)
Recent studies demonstrate that rapid antidepressant response to ketamine is mediated by activation of the mammalian target of rapamycin (mTOR) signaling pathway, leading to increased synaptic proteins in the prefrontal cortex (PFC) of rats. Our postmortem studies indicate robust deficits in prominent postsynaptic proteins including N-methyl-d-aspartate (NMDA) receptor subunits (NR2A, NR2B), metabotropic glutamate receptor subtype 5 (mGluR5) and postsynaptic density protein 95kDa (PSD-95) in the PFC in major depressive disorder (MDD). We hypothesize that deficits in the mTOR-dependent translation initiation pathway contribute to the molecular pathology seen in the PFC of MDD subjects, and that a rapid reversal of these abnormalities may underlie antidepressant activity. The majority of known translational regulation occurs at the level of initiation. mTOR regulates translation initiation via its downstream components: p70-kDa ribosomal protein S6 kinase (p70S6K), and eukaryotic initiation factors 4E and 4B (eIF4E and eIF4B). In this study, we examined the expression of mTOR and its core downstream signaling targets: p70S6K, eIF4E, and eIF4B in the PFC of 12 depressed subjects and 12 psychiatrically healthy controls using Western blot. Levels of eIF4E phosphorylated at serine 209 (p-eIF4E-Ser209) and eIF4B phosphorylated at serine 504 (p-eIF4B-Ser504) were also examined. Adjacent cortical tissue samples from both cohorts of subjects were used in our previous postmortem analyses. There was a significant reduction in mTOR, p70S6K, eIF4B and p-eIF4B protein expression in MDD subjects relative to controls. No group differences were observed in eIF4E, p-eIF4E or actin levels. Our findings show deficits in mTOR-dependent translation initiation in MDD particularly via the p70S6K/eIF4B pathway, and indicate a potential association between marked deficits in synaptic proteins and dysregulation of mTOR signaling in MDD. ► We used postmortem cortical tissue to examine mTOR signaling in depression. ► Reductions in mTOR, p70S6K, eIF4B and p-eIF4B were identified. ► No differences were seen in eIF4E, p-eIF4E or actin levels. ► Specific dysregulation of mTOR/p70S6K/eIF4B signaling is evident in depression. ► Dysfunction of mTOR signaling may underlie synaptic deficits in depression.